Corporate finance, industrial performance and environment in Africa: Lessons for policy - Peter Ekundayo Mesagan; Titilope C. Adewuyi; Olugbenga Olaoye (African Governance and Development Institute (AGDI), 2022)
This study employs the Pool Mean Group framework to investigate the impact of corporate finance and industrial performance on pollution in Africa between 1990 and 2020. The study, which focuses on 36 African nations, found that corporate financing insignificantly enhances environmental quality in the short run, while it significantly worsens the environment in the long run. Also, the result shows that industrial performance exerts a negative but insignificant impact on pollution in both the short- and long-run periods. Lastly, the interaction term between corporate finance and industrial performance has a negative and significant impact on pollution in both periods. With this striking result, the study recommends that efforts should be made to promote the growth of environmentally sound production plants in the continent through the removal of credit facilitation bottlenecks.
Keywords: G3; L25; O14; Q53; 330; Corporate Finance; Industrial Performance; Pollution; Africa